UPAYA MENINGKATKAN HASIL PEMBELAJARAN IPS MELALUI PENERAPAN MODEL GRUP INVESTIGATION SISWA KELAS V SDN 1 TALANG TELUK BETUNG SELATAN BANDAR LAMPUNG - Helnawati, Helnawati (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
The purpose of this study was to improve the quality of social studies learning through the Group Investigation model in class V SDN 1 Talang Teluk Betung Selatan Bandar Lampung. To achieve the research objectives mentioned above, the author uses the research method